2000
DOI: 10.1074/jbc.m910187199
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Functional Expression of Two Families of β-Subunits of the Large Conductance Calcium-activated K+ Channel

Abstract: We report here a characterization of two families of calcium-activated K ؉ channel ␤-subunits, ␤2 and ␤3, which are encoded by distinct genes that map to 3q26.2-27. A single ␤2 family member and four alternatively spliced variants of ␤3 were investigated. These subunits have predicted molecular masses of 27.1-31.6 kDa, share ϳ30 -44% amino acid identity with ␤1, and exhibit distinct but overlapping expression patterns. Coexpression of the ␤2 or ␤3a-c subunits with a BK ␣-subunit altered the functional properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
252
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(264 citation statements)
references
References 40 publications
10
252
2
Order By: Relevance
“…We showed previously that DHA increased currents through native BK channels in vascular smooth muscle cells as well as heterologously expressed Slo1+β1 channels (27). Here we examined whether DHA stimulates Slo1 channels with other subunit compositions: Slo1 alone, Slo1+β2 (18,19), Slo1+β4 (6), and Slo1+LRRC26 (γ1) (3,4). Because coassembly with wild-type β2 introduces inactivation mediated by the β2 N terminus in the resulting channel complex (35), we also examined the impact of β2 with a deletion in the N terminus (Δ2-19) to remove inactivation (18,19).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We showed previously that DHA increased currents through native BK channels in vascular smooth muscle cells as well as heterologously expressed Slo1+β1 channels (27). Here we examined whether DHA stimulates Slo1 channels with other subunit compositions: Slo1 alone, Slo1+β2 (18,19), Slo1+β4 (6), and Slo1+LRRC26 (γ1) (3,4). Because coassembly with wild-type β2 introduces inactivation mediated by the β2 N terminus in the resulting channel complex (35), we also examined the impact of β2 with a deletion in the N terminus (Δ2-19) to remove inactivation (18,19).…”
Section: Resultsmentioning
confidence: 99%
“…Here we examined whether DHA stimulates Slo1 channels with other subunit compositions: Slo1 alone, Slo1+β2 (18,19), Slo1+β4 (6), and Slo1+LRRC26 (γ1) (3,4). Because coassembly with wild-type β2 introduces inactivation mediated by the β2 N terminus in the resulting channel complex (35), we also examined the impact of β2 with a deletion in the N terminus (Δ2-19) to remove inactivation (18,19). Pore-forming Slo1 and auxiliary subunits were coexpressed in human embryonic kidney (HEK) cells and studied using the inside-out patch-clamp method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BK channels are noninactivating K + channels, except in the presence of a β2 or β3 auxiliary subunit whose N-terminal peptide sequence occludes the channel pore in a more N-type inactivation manner (31)(32)(33). We found that, even under nearly K + -free conditions in the external recording solution, WT BK channels did not show any significant inactivation up to 10 s. The presence of Tyr at the BK channel 294 position (equivalent to the 449 position in Shaker channels) might partly contribute to the noninactivation because the T449Y mutation slows down C-type inactivation in Shaker channels (25).…”
Section: Discussionmentioning
confidence: 99%
“…Functional BK channels (also called maxi-K or slo channels) are tetrameric structures consisting of four pore forming ␣ subunits (the principal subunits). In addition, four different ␤ subunits (auxiliary subunits) have been identified (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%